2018
DOI: 10.1007/s10336-018-1601-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotyping by sequencing for population genetics of sibling and hybridizing birds: an example using Syrian and Great Spotted Woodpeckers

Abstract: Recent high-throughput genotyping technologies allow for comprehensive genomic analyses on an unprecedented scale. However the advantages of the most commonly used tools are strongly limited in non-model organisms, including wild birds. In this study we attempt to test the utility of genotyping by sequencing (GBS) without relying on the reference genome sequence in selected pairs of sibling bird species that are known to hybridize (Syrian and Great Spotted Woodpeckers). We found that GBS is able to produce a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Moreover, it is important to mention that GBS was also successfully used in Pekin duck, which is genetically close to a goose as they are in the same biological family, Anatidae [ 21 ]. Gurgul et al (2019) also indicated a satisfying result of GBS being used in woodpeckers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is important to mention that GBS was also successfully used in Pekin duck, which is genetically close to a goose as they are in the same biological family, Anatidae [ 21 ]. Gurgul et al (2019) also indicated a satisfying result of GBS being used in woodpeckers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its scientific contribution to understanding the mechanisms of hybridization in birds, the present case could have other serious implications. Hybridization is frequent between Syrian and Great Spotted Woodpeckers (Michalczuk et al 2014, Figarski & Kajtoch 2018b, Gurgul et al 2019. Knowing that hybrids and backcrosses are viable and fertile, this could present a serious threat to the duration of Syrian Woodpecker populations on the verge of the species range in central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…2014, Figarski & Kajtoch 2018b, Gurgul et al . 2019). Increasing cases of territory overlap and mixed pairs abundance are also being reported (Figarski & Kajtoch 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear SNPs became highly attractive as genetic markers. In particular, they were successfully used in studies of hybridization in numerous non-model animal groups, e.g., in woodpeckers (Gurgul et al, 2019), mountain and brown hares (Levanen et al, 2018), wild and domestic cats (Oliveira et al, 2015), Peromyscus mice (Garcia-Elfring et al, 2017), chiffchaffs (Shipilina et al, 2017), warblers (Brelsford et al, 2017), sparrows (Elgvin et al, 2017), and American crows (Slager et al, 2020).…”
Section: Introductionmentioning
confidence: 99%